Characteristics of common code conducted emission of multi-boost converters - Sudrajat, Muhammad Imam; Nuvus, Afiva Riyatun; Mandaris, Dwi (National Research and Innovation Agency, 2023)
One of the primary challenges faced when utilizing power converters such as a DC boost converter is electromagnetic interference (EMI) issues, one of which is common-mode (CM) noise. In order to mitigate the unwanted EMI from converters and design proper EMI filters, it is imperative to possess comprehensive insight into the characteristics of CM noise generated from the converters. This study presents the investigation regarding the characteristic of CM noise emitted by multi-boost converters when operated under varying duty cycle conditions. The research was conducted by measuring and analyzing the CM noise generated by three identical boost converters arranged in a parallel configuration. The result shows that the amplitude of each harmonic of CM noise generated by the multi-boost converters is 5 dB to 10 dB higher than CM noise from a single-boost converter. This is due to each converter being configured in the same conditions, producing a constructive interaction of the generated CM noise. Moreover, the duty cycle of pulse-width modulation (PWM) has a strong influence on the characteristic of the amplitude of each harmonic frequency. It is proven by the amplitude pattern of each harmonic of CM noise. Under duty cycle variations, the converters generate similar peaks and valley amplitude patterns as the Fourier transformation of the trapezoidal waveform used in the PWM setting.